2019
DOI: 10.1007/s11661-019-05472-x
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Primary Alpha Plate Growth in Titanium Alloys

Abstract: The kinetics of primary α-Ti colony/Widmanstätten plate growth from the β are examined, comparing model to experiment. The plate growth velocity depends sensitively both on the diffusivity D(T ) of the rate-limiting species and on the supersaturation around the growing plate. These result in a maxima in growth velocity around 40 K below the transus, once sufficient supersaturation is available to drive plate growth. In Ti-6246, the plate growth velocity was found to be around 0.32 µm min −1 at 850 • C, which w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Ta exhibits slower diffusion rate in high temperature β-Ti as the concentration of Ta increases [182]. Such sluggish diffusion of Ta can become a limiting factor for the growth rate of lath/acicular phase which subsequently leads to finer microstructure [183]. The observed microstructure refinement is consistent with a similar Ti-Ta study previously done [123].…”
supporting
confidence: 87%
“…Ta exhibits slower diffusion rate in high temperature β-Ti as the concentration of Ta increases [182]. Such sluggish diffusion of Ta can become a limiting factor for the growth rate of lath/acicular phase which subsequently leads to finer microstructure [183]. The observed microstructure refinement is consistent with a similar Ti-Ta study previously done [123].…”
supporting
confidence: 87%
“…However, Ti6242 is alloyed with molybdenum, which has a much slower solid-state diffusivity than vanadium, the slowest diffusing species in Ti64. [26] When compared to Ti64, this difference in diffusivity is known to impede the b-grain growth kinetics, [56,58,59] and the growth rate of a laths during the b fi a transformation [60] ; so it is perhaps not surprising that Ti6242 was found to have an overall more refined microstructure. Given that both materials were built with near-identical thermal histories, with multiple-heating cycles above and below the b transus, where the b grains and a + b transformation microstructure have ample opportunity to coarsen, the results demonstrate that the presence of slower-diffusing alloying additions in titanium alloys like Ti6242 appear to be advantageous for refining the as-deposited microstructure in a high-deposition-rate AM process, which have higher heat inputs and lower cooling rates than more conventional AM platforms, such as powder bed.…”
Section: Discussionmentioning
confidence: 99%
“…[28,36] The growth rate of a laths at a given undercooling is dependent on partitioning of the slowest diffusing species in each alloy between a and the b matrix, which will try to maintain equilibrium at the a/b interface. [60] The dominant elements that control the a growth kinetics are thus vanadium for Ti64 and molybdenum for Ti6242. [26,27,52,53,68] Given that molybdenum has the slowest diffusivity by far in titanium, the a plates in Ti6242 will grow more slowly than in Ti64, [60] allowing more nucleation and thus an overall finer basketweave microstructure.…”
Section: B Transformation Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have declared [ 42 ] that the features of both shear and diffusion mechanisms are typical of titanium alloys and high-alloyed steels. Other studies have described each transformation mechanism in detail and strictly divide diffusion and shear [ 8 , 10 , 22 , 43 , 44 ]. However, it has been demonstrated that the BOR is followed for all transformation mechanisms [ 18 , 23 , 43 , 45 ].…”
Section: Introductionmentioning
confidence: 99%